Mixed Quadrature Rule for Double Integrals of Simpsons 1/3rd and Gauss Legendre two Point Rule in two Variables (Global Journal of Science Frontier Research, 2016)
In this article we are concerned with mixed quadrature rule of higher degree of precision for double integrals with double variables. The rule is numerically tested taking some suitable texts and the error bound is determined.
Keywords: mixed quadrature rule; maclaurin2019; s theorem; error bound; degree of precision